AMF30a promotes survival and function of human corneal endothelial cells by regulating TGF-β/ROCK/HIPPO pathway - Yunkyoung Ryu; Hye-Jin Son; Jin Sun Hwang; Kyung Bo Noh; Sun-Hee Oh; Eun-Kyoung Choi; Young Joo Shin (Scientific Reports)
Abstract Corneal endothelial cells (CECs), located in the innermost layer of cornea, are crucial for maintaining its transparency. Peptidylarginine deiminase 2 (PAD2) is an enzyme responsible for catalyzing the post-translational modification of arginine into citrulline, a process known as citrullination. In this study, we investigated the effect of AMF30a, PAD2 inhibitor, on survival and function of CECs. Cultured human CECs (hCECs) were treated with AMF30a, followed by treatments with or without AMF30a under transforming growth factor-beta (TGF-β). Cells were cultured from donor corneas and analyzed for viability (CCK-8), proliferation (BrdU assay), cytotoxicity (LDH assay), and oxidative stress (DCF-DA). Adhesion and morphology were evaluated via crystal violet staining and imaging software. Western blot and immunofluorescence identified protein expression and localization. RNA sequencing revealed differentially expressed genes, with functional enrichment via GO analysis. AMF30a enhanced cell viability, proliferation, and adhesion while reducing cytotoxicity and oxidative stress. Morphological analysis revealed reduced cell size and elongation factor, indicating structural changes. AMF30a modulated the HIPPO signaling pathway by increasing YAP phosphorylation and reducing its nuclear translocation, while downregulating ERK1/2 activation. Transcriptome analysis identified differentially expressed genes (DEGs) associated with AMF30a treatment, highlighting pathways related to GPCR signaling and protein targeting. Additionally, AMF30a counteracted TGF-β-induced effects, including increased oxidative stress, citrullination, and ROCK/HIPPO signaling activation, thereby promoting cell cycle progression and reducing senescence. PAD2-mediated citrullination is essential for TGF-β/ROCK/HIPPO signaling pathway. AMF30a promoted the proliferation and protected against TGF-β-induced senescence in hCECs, suggesting that PAD2 plays a significant role in the survival and function of hCECs. Thus, AMF30a may be a promising therapeutic strategy for hCEC diseases.